Comparison Between Outcomes of Rubber Band Ligation vs Hemorrhoidectomy in Treatment of Third-Degree Hemorrhoids - Jameel, Zaigham; Anwar, Muhammad Imran; Zulfiqar, Ghazanfar; Ikram, Muhammad Ammar; Khan, Muzammil; Ikram, Yousma; Ghazanfar, Saqlain (Biological and Clinical Sciences Research Journal, 2025)
Hemorrhoids are a common anorectal disorder affecting a significant proportion of the population, particularly those with chronic constipation or increased intra-abdominal pressure. Third-degree hemorrhoids are symptomatic and often require intervention. Rubber Band Ligation (RBL) and Hemorrhoidectomy are commonly used treatment modalities with differing outcomes and complications. Objectives: To compare the outcomes of Rubber Band Ligation versus Hemorrhoidectomy in treating third-degree hemorrhoids, focusing on postoperative pain, complications, recurrence rates, and patient satisfaction. Methodology: A comparative observational Study was conducted at the Department of General Surgery, Sheikh Zayed Hospital, Lahore, from December 2023 to November 2024. A total of 120 patients diagnosed with third-degree hemorrhoids were included, with 60 patients undergoing RBL (Group A) and 60 undergoing Hemorrhoidectomy (Group B). Patients were selected using a non-probability consecutive sampling technique. Pain assessment was performed using the Visual Analog Scale (VAS) at 1 week, 4 weeks, and 12 weeks postoperatively. Complications, recurrence rates, and patient satisfaction were recorded. Data analysis was performed using SPSS version 25, and a p-value of <0.05 was considered statistically significant. Results: RBL showed significantly lower postoperative pain at all follow-up periods compared to Hemorrhoidectomy (p<0.001). Recurrence rates were higher in the RBL group (20%) compared to the Hemorrhoidectomy group (5%) (p=0.014). Hemorrhoidectomy patients reported higher satisfaction levels, while RBL had shorter hospital stays and fewer immediate postoperative complications. Conclusion: Rubber Band Ligation is an effective and minimally invasive option with reduced pain and shorter hospital stays, while Hemorrhoidectomy provides lower recurrence rates and higher patient satisfaction. Treatment choice should be individualized based on patient preferences and clinical judgment.